MEDIA PROMOSI PERILAKU HIDUP BERSIH DAN SEHAT (PHBS) DI KAWASAN WISATA DANAU TOBA - Destanul Aulia; Sri Fajar Ayu (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2018)
Human resources in ​​Lake Toba should be built along with the attention and development of natural tourism potential of Lake Toba, that has been given by the government. One of the steps is through education about clean and healthy behavior. This education can be done through the promotion of clean and healthy life behavior for the people of Lake Toba, both in physical and non-physical form. This program is aimed at promoting clean and healthy living behavior (PHBS) through PHBS promotional media created by involving local potency in Lake Toba by use a community figure, institution / institution like Alusi Tao Toba. The method of implementation of this program is to create a media promotion of PHBS by involving local potential and discussion lecture method for training activities of public figures and institutions about PHBS by using media campaign that has been made. The result of the implementation of this activity is the existence of simple and interesting PHBS manual and given to Alusi Tao Toba. In addition, PHBS promotional videos and PHBS banners for PHBS promotional media have been established in Lake Toba area through a partnership.